Identification of Residues within Flavivirus Non-Structural Protein Associated with Mosquito Transmission. Issue 5 (27th May 2022) - Vamos, Boglarka; Cheung, Yin; Maringer, Kevin
Abstract : Flavivirus non-structural protein 1 (NS1) is present at high levels in patient blood and has been previously implicated in increasing virus acquisition by mosquito vectors, which may facilitate increased transmission. Therefore, flaviviruses transmitted by Aedes aegypti mosquitoes were hypothesised to have similarities within NS1, and potentially other NS proteins, that may correlate with mosquito-borne (rather than tick-borne or no vector) transmission. Representative flavivirus amino acid sequences were downloaded from the NCBI Protein database, aligned using viprbrc.org and then manually analysed to identify residues correlating with arthropod vector tropism. All available sequences for individual clinically important flaviviruses were then analysed on viprbrc.org to determine sequence conservation within viral species for those residues correlating with vector tropism. Overall, we found five residues in NS1 that were highly correlated with transmission by mosquitoes, had functionally relevant differences in amino acid side chain properties between mosquito- and tick-borne viruses and had conservation within viral species. Additionally, a further nine residues in NS3 and four residues in NS4A were identified using the same methodology. Importantly, for NS1, for which more data is available regarding its role in influencing transmission, the residues we identified have not been implicated in increased transmission thus far. Hence, future work would aim to test the impact of mutating these NS1 residues to elucidate whether they modulate NS1 secretion into the blood stream, virus replication and/or transmission. Gaining an understanding of the molecular determinants underpinning vector tropism could be useful in the creation of transmission-incompetent vectors.